RAINFALL ANALYSIS IN MICROWATERSHEDS OF UPPER DAMODAR VALLEY - Reddy, K.S.; Rao, K.V.R.; Singh, R.M; Bhattacharya, A.K. (Journal of Soil and Water Conservation, 2022)
Daily rainfall data of 20 years (1972-91) was collected from the local obsentories of Bishnugadh in Upper Damodar Valley. The data are analysed by fitting different distributions like Normal. Lognormal (LN), Log Pearson-111 (LP-111) Gumbel and Gamma. One day maxi/num, weekly, monthly and seasonal rainfall data are fitted in the above distributions and their corresponding rainfall events are estimated at 20, 40, 60 and 80% probabilities of exceedence. From the present rainfall analysis, it is observed that, Gumbel followed by Gamma are identified the best for one day maximum rainfall; Log Normal for weekly rainfall; Gumbel for monthly rainfall and Normal, Gumbel and Log Normal for seasonal rain all. The above inferences are drawn based on the minimum D-index values obtained in the analysis.